HUMAN RIGHTS IN THE SYSTEM OF BASIC EUROPEAN VALUES - Makeieva, Оlena (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Purpose: to explore the theoretical and legal foundations of respect for human rights in the system of basic European values. Research methods: general scientific methods of analysis, synthesis and generalization; comparative law, philosophical, historical, special law. Results: on the basis of the study and analysis of European legislation, the analysis of the basic basic values of the European Union was identified and analyzed, including: respect for human dignity, freedom, democracy, equality, rule of law, respect for human rights; their essence and content in the conditions of European integration processes in Ukraine are revealed. In today's world, these basic values must be clear to every Ukrainian, as they unite Ukrainian society with Europeans more than even laws or intergovernmental agreements. European values are worldview principles on the basis of which reforms are carried out in Ukraine, which will allow citizens to live in a comfortable and safe country, travel and study freely, and know that the state has uniform laws. It is up to each of us to move towards membership of the European Union. It is the European worldview based on values - is the basis of the well-being of the European Union, and Ukraine's European integration is a change in worldview principles at all levels of life and a movement towards European well-being. Discussion: today, the path of the EU is taking place at a very tragic time, when many Ukrainians who profess European values are losing their lives defending Ukraine's independence and sovereignty in the fight against the Russian aggressor. We believe that Ukraine will win, become a candidate for accession, given the price it paid on the path to independence and democracy. It is obvious that scientific and legal education in the field of human rights is a vital condition for building respect for human rights and preventing their violation, which will be an important contribution to building a civil society that respects the rights of each member, with a high level of legal culture. and civic consciousness.